The image of Brazil: a quantitative study from the perspective of latin american consumers - Sarzuri Ayala, Daisy Carmen; Correa, Caroline Miranda [UNESP]; Merlo, Edgard Monforte [UNESP]; Silva, Dirceu da; Braga Junior, Sergio Silva [UNESP] (Univ Nove Julho, 2019)
Purpose: The objective of this study is to investigate the dimensions that make up the image of Brazil, specifically in Latin America. Method: A quantitative exploratory research has been carried out through a survey with a sample of 1617 respondents of Mexican, Argentinean, Ecuadorian and Bolivian nationality. Data analysis has been performed using structural equation modeling using SmartPLS 2.0 M3 software. Originality/Relevance: The originality of this study is to evaluate the perception of Latin American for the image of Brazil since studies of this type have not yet performed. Thus, the research contributes with an interdisciplinary study whose scale and similar studies can use methodology. Results: The results of the study confirmed that the Brazilian image could be analyzed by a combination of the cognitive, affective and conative components. Since cognitive was the most strongly identified component, based principally on beliefs related to politics, people in the country, socio-environmental aspects, economy, innovation and culture in Brazil. Theoretical/Methodological Contributions: The methodology of data analysis used reinforces how much the Modeling by Structural Equations can contribute to the development of the theory related to the image of a country. As for the theoretical advance, it was possible to observe the importance of studies on the subject. Social/Management contributions: The main contribution of this study is the possibility of companies using these results in the direction of efforts in marketing campaigns and image of products for the external or internal market.
Keywords: Consumers; Country image; Brazil's image